Big Data: Actuality and Challenges: Array - Barila, Adina; Danubianu, Mirela; Turcu, Corneliu-Octavian (Journal of Danubian Studies and Research, 2021)
The volume of data is constantly growing due to the explosion of machine-generated data and human involvement in social networks, especially in the last period in which the pandemic forced most activities to take place online. Big Data refers to storage, manipulation and analysis of this huge data sets that come from variety of sources and are too large and too heterogeneous to be traditionally processed. This paper gives an overview of Big Data sources, Big Data analytics, its applications, advantages and limitations, and challenges that Big Data has to face nowadays.